Proses Perceraian Dari Perkawinan Yang Tidak Terdaftar Di Pengadilan Agama Kelas IB Pariaman - Ramadhan, Rezky (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This article aims to find out the factors that cause unregistered marriages, the process, and the legal consequences of divorce from marriages that have been legalized at the Religious Court class IB Pariaman. The problem is focused on divorce from unregistered marriages which is a real problem in society, especially in the area of the Religious Courts of Pariaman. To approach this problem, the research method used in this article is sociological juridical, namely field studies to obtain primary data in the field of law which will be analyzed with laws and regulations related to the divorce process in marriages that are not registered at the Pariaman religious court class IB. The data was collected through in-depth interviews with related parties, such as the young clerk of the legal division of the Class IB Pariaman religious court. In this in-depth interview, the questions were used as an interview guide and the mobile phone was used as a voice recorder during the interview and analyzed in a descriptive analysis where the research did not only provide an overview but also wrote down and reported an object that became a legal event which would draw general conclusions in the case. researched. This study concludes that the legal consequences that result in divorce from a marriage that has been entered into are in terms of child custody, such as losing the right to have a loss certificate, and in terms of inheritance, such as the wife not receiving inheritance rights from her husband.